FAMILY INTEGRATION IMPACT ON THE LEARNING OF SEVENTH GRADE STUDENTS - Cedeño, Gema Mireya Loor; Zambrano, Lilia Moncerrate Villacis (Seven Editora, 2025)
The objective of the research work was to analyze family integration and its impact on the learning of students in the seventh year of elementary school, the methodology was framed from the inductive-deductive, analytical, synthetic, historical-logical methods with a descriptive, qualitative-quantitative approach, the techniques used were student surveys, interview with the tutor teacher and interview with the director, it was tabulated in the SPCS 29 and a level of reliability of the instrument according to Cronbach’s Alpha at 0.83 was obtained. One of the most relevant conclusions was that there is a considerable percentage of children who are affected by the lack of integration in their homes and it is concluded that the integration of students into their family nucleus is always reflected in their school performance, behavior, grades, mode of socialization and psychological behavior in group and family behaviors. What was evidenced is that the impact of family integration and its incidence on the learning of elementary school students are key to the harmonious development in meaningful learning and in the integral development of each student. DOI: https://doi.org/10.56238/sevened2024.037-198